The Dynamics of Adaptation, Resistance, and Linguistic Identity Shifts Among Muslim Communities in the Context of Social Media - Qatrunnada, Aliya; Hayati, Ana; Ilmi, Bachrotul; Shovia; Rachmawati, Usi Al Falach (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study investigates the dynamic interaction between the Arabic language, digital platforms, and the evolution of linguistic identity within Muslim communities. Using a digital sociolinguistic approach and analyzing social media content, the study examines how Arabic—as both a sacred language and a cultural symbol—adapts to technological advancement. The findings reveal a dual process: adaptation and resistance. On one hand, adaptation is reflected in creative linguistic innovations such as Arabizi (a combination of Latin script with Arabic phonetics) and digitally optimized Arabic calligraphy, which facilitate communication in multilingual online spaces. These practices represent a pragmatic response to globalized digital interaction while maintaining cultural relevance. On the other hand, resistance emerges through grassroots efforts to preserve classical Arabic script, especially among religious and educational communities who regard linguistic purity as an integral part of Islamic heritage. This tension illustrates an ongoing negotiation between tradition and modernity. The study highlights the role of language as a mediator of culture and innovation in the digital age. Digital communication becomes a contested space where language choices reflect struggles over authenticity, identity, and globalization—while also showcasing the resilience of religious linguistic practices amid technological disruption.